Universities as Human Rights Actors. (9th May 2019) - Brems, Eva; Lavrysen, Laurens; Verdonck, Lieselot
Abstract: This policy and practice note explores the possibilities of a vision of human rights protection that conceives of universities as human rights actors. This vision is situated in the broader human rights context, in which it is increasingly recognized that non-traditional human rights actors, rather than only the central government level, also bear responsibilities in the field of human rights. Given their crucial societal role, it is argued that universities should similarly take up their human rights responsibility. This note will present the case study of the human rights policy of Ghent University (Belgium), which applies to that university's international relations, as a good practice of how the human rights responsibility of universities can be operationalized. The paper concludes with a number of critical reflections.